A Note on Background Subtraction by Utilizing a New Tensor Approach - IÅÄ±k, Åahin; Ãzkan, Kemal; DoÄan, Muzaffer; Gerek, Ãmer Nezih (Prof. Dr. Ismail SARITAS, 2016)
This study deals with determining the foreground region by background subtraction based on a new tensor decomposition method. With this aim, the concept of Common Matrix Approach (CMA) is utilized with a purpose of background modelling. The performance of proposed method is validated by making experiments on real videos provided by Wallflower dataset. The obtained results are compared with well-known methods based on subjective on objective evaluation measures. The obtained good results indicate that using the CMA algorithm for background modelling is a simple and effective technique in terms computational cost and implementation. As an eventual result, we have observed that the superior results are determined on complex backgrounds including dynamic objects and illumination variation in image sets.